Structural designing, spectral and computational studies of bioactive Schiff's base ligand and its transition metal complexes. (5th July 2017) - Gautam, Seema; Chandra, Sulekh; Rajor, Hament; Agrawal, Swati; Tomar, Praveen Kumar
Abstract: Transition metal complexes of Mn(II) and Ni(II) have been synthesized with novel bioactive Schiff's base ligand. Schiff's base ligand i.e. benzoylacetone‐bis(2‐amino‐4‐methylbenzothioazole) has been synthesized via condensation reaction between 2‐amino‐4‐methylbenzothioazole and benzoylacetone in 2:1 ratio, respectively. Synthesized ligand has been characterized using elemental analysis, infra‐red, 1 H–NMR and mass spectroscopy techniques. Characterization of complexes was based on magnetic moment, molar conductance, elemental analysis, electronic spectra, infra‐red and EPR spectroscopic techniques. Molar conductance data suggest that metal complexes are non‐electrolytic in nature. Therefore, these complexes are formulated as [M(L)X2 ], where M = Mn(II), Ni(II), L = Schiff's base ligand, X = Cl −, CH3 COO −, NO3 − . Data of characterization study suggest octahedral geometry for Mn(II) and Ni(II) complexes. Geometry of metal complexes was also optimized with the help of computational study i.e. molecular modelling. Computational study also suggests octahedral geometry for complexes. Free ligand as well as its all metal complexes have been screened against the growth of pathogenic bacteria ( E.coli, S.aureus ) and fungi ( C.albicans, C.krusei, C.parapsilosis, C.tropicalis ) to assess their inhibition potential. The inhibition data revealed that metal complexes exhibit higher inhibition potential against the growth of bacteria and fungi microorganisms than free ligand. Abstract : Synthesis and characterization of novel bioactive Schiff's base ligand and its metal complexes were done by various spectral techniques, molecular modelling. On the basis of characterization study data, metal complexes possess six coordinated octahedral geometry. Thermal data suggested that metal complexes are more thermal stable than free Schiff's base ligand. In vitro antibacterial and antifungal activity of synthesized ligand and its metal complexes were screened. All metal complexes were more biologically sensitive than ligand against the growth of microorganism.